Nanoparticle‐mediated siRNA delivery systems for cancer therapy. Issue 3 (11th February 2021) - Gao, Han; Cheng, Ruoyu; A. Santos, Hélder
Abstract: The small interfering RNA (siRNA)‐based therapeutics have raised great attention since the first RNA interference (RNAi)‐derived drug, patisiran, was approved by the US Food and Drug Administration, which represented a landmark in the field of gene therapy. Given the properties of interfering disease‐associated gene expression, RNAi machinery is regarded as an essential factor for preparing precise medicine. However, over the past few years, siRNA drugs are undergoing a period of clinical translation, in which the major hurdle is the limited efficient delivery strategies. Therefore, this mini‐review mainly focuses on describing the state‐of‐the‐art of the nanoscale platforms for delivering siRNA payloads, also addressing their applications in cancer therapy. Finally, the status of siRNA drugs under clinical trials is discussed, providing a comprehensive understanding on the field of oligonucleotide‐mediated therapeutics. Abstract : Gene therapy is drawing great attention due to the possibility of molecule‐manipulation efficacy, such as the RNA interference (RNAi)‐based therapeutics. In this mini‐review, we describe the fundamental mechanisms of RNAi machinery and provide insights on the current status of nanoparticles for siRNA delivery, as well as to discuss the applications of siRNA in cancer research and clinical therapy.